Arethe Sociologistswell prepared to the Modern War (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This article is one additional indication that a new realm of multi-sided and trans-disciplinary sociological studies is emerging within the interrelated scope of social, technical and natural sciences. How Russian sociology will respond to this cworld challenge of the new times? Do the sociologists and political scientists well prepared to the modern cold or hot war, to a variety of small and middle-scale wars under conditions of globalization and the development of the IT technologies, on the one hand, and separatism and a tough global struggle for resources and political domination, on the other? Are the new political subjects that have emerged as a result of such wars legitimate? The article presents the authors reflection on these and other critical ˜turning points of the world and Russian sociology and practice.